Matching different-structured advertising pictorial metaphors with verbalization forms: incongruity-based evoked response potentials evidence - Cao, Shuo; Yue, Fang; Zheng, Shihui; Fu, Yang; Huang, Jing; Wang, Huili (Frontiers in Psychology, 2023)
Using evoked response potentials (ERP), this study intends to identify the optimal verbalization forms for pictorial metaphors. A 3 (pictorial structure: fusion, juxtaposition, literal image) × 2 [verbalization form: A是(is) B, A像(is like) B] within-group experiment was conducted among thirty six participants. ERPs were time-locked to the onset of the verb [是/像(is/ is like)] of the metaphor sentence that follows a pictorial metaphor to detect the verbo-pictorial incongruity in metaphor comprehension. The incongruity-based ERP analysis showed that pictorial metaphors, when verbalized in two forms, all induced frontal N1 effect, regardless of pictorial structures, only with a larger N1 amplitude for literal images in “A是(is) B”. A central stronger P2 was observed in “A像(is like) B” for three structures. Despite a general elicitation of posterior P3 in all conditions, a larger P3 was found for juxtapositions verbalized in “A像(is like) B” and for literal images verbalized in “A是(is) B”. There was no significant difference between two verbalization forms for fusion-structured pictorial metaphors. These findings suggest: (1) verbo-pictorial metaphors could induce incongruity-based attention; (2) higher verbo-pictorial semantic congruity and relatedness, indexed by stronger P2 and P3, confirmed “A像(is like) B” to be the more effective verbalization form in representing pictorial metaphors, specifically for juxtaposition-structured pictorial metaphors; (3) for non-metaphor advertising pictures, verbal metaphor showed an interference effect. The study not only reveals the neuro-cognitive mechanism of processing verbo-pictorial metaphors, but also offers neural reference for the design of effective multi-modal metaphor by finding an optimal match between PMs and verbalization forms.